Handbook of Education Policy Studies Values, Governance, Globalization, and Methodology, Volume 1 - Fan, Guorui; Popkewitz, Thomas S. (Springer Nature Singapore : Imprint: Springer, 2020)
This open access handbook brings together the latest research from a wide range of internationally influential scholars to analyze educational policy research from international, historical and interdisciplinary perspectives. By effectively breaking through the boundaries between countries and disciplines, it presents new theories, techniques and methods for contemporary education policy, and illustrates the educational policies and educational reform practices that various countries have introduced to meet the challenges of continuous change. Based on an analysis of the nature of education policy and education reform, this volume focuses on education reform and the concept of education quality. Adopting a historical and comparative perspective, it examines the dialectical relationship between education policy and education reform in various countries, assesses theoretical and practical issues in the process of moving from regulation to multiple governance in contemporary education administration, and explores the impact of globalization on national education reform and the interdependence between countries. In addition, it presents studies addressing educational policy research methodology from multiple perspectives. Highlighting the changes in national education macro policies, this volume comprehensively reveals the complex relationship between contemporary education reform and social change, and explores the links between contemporary social, political and economic systems and educational policy research and practice, offering a holistic portrait of macro trends in contemporary education reform.